Application of Cellulose Acetate Propionate Biopolymer Membrane in The Treatment of Textile Wastewater Containing Remazol Dye - Amilia, Amilia; Maryudi, Maryudi; Rahayu, Aster; Hakika, Dhias Cahya; Suradi, Siti Samahani (Jurnal Bahan Alam Terbarukan, 2024)
Textile liquid waste is pollution resulted from textile industry activities that often produce hazardous and toxic materials. Therefore, appropriate processing techniques are needed. There are many processing methods that can be used in treating this textile liquid waste, one of which is using membrane technology with phase inversion techniques. Membrane technology has advantages over other processing methods such as, being biopolymeric, relatively lower energy consumption, does not use chemicals in the processing process, and does not cause new waste in the processing process.  In this study, 3 variations of cellulose acetate propionate (CAP) concentration were carried out in the manufacture of membranes including, 13% CAP; 14% CAP; and 15% CAP. Membranes that have been made are then carried out several analyses, namely porosity analysis; flux analysis; rejection analysis; and color concentration reduction analysis. The results in this study found that the highest porosity value, rejection value and flux value were found in the CAP membrane with a concentration of 13%.  The CAP membrane has the best rejection value on reducing the remazol concentration of 43% with a membrane of 13% CAP.